أثر التعلق بالشعر العربي الجاهلي في التحلي بالقيم العلية العفة والمروءة أنموذجين - نصر الدين, أجدير (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2024)
Let no one doubt that the Arabs were of sound nature and attained the reins of perfection in matters of morality, and there is no dispute that the laws came to perfect the virtues of morality and demonstrate its high status in preserving the order of nations. Rather, the one who examines the texts of legislation finds that the fruits of its rhythm purify and refine souls, and morals are the angel of command. For the Arabs in pre-Islamic times, in order to achieve it, they spent countless amounts of time and money and fought wars and horrors. (1) In explaining the meanings of the search terms, the Arabic language has accustomed us to the abundance of vocabulary and its contempt. Perhaps it is important in this research to mention the terms that the Arab used in expressing the sublime and sublime morals to which he was accustomed and which his thought concluded as a source of pride and a standard for goodness. (2) Poetic evidence devoted to the meanings of chastity and jealousy. One of the finest manifestations of chivalry is jealousy and chastity among the Arab, and this is necessary for pride and pride in honor and the preservation of honor. History has told us that transgressing against the honor of the Arab leads to wars whose fires do not subside. At the end of the tour with this brief research on the chastity of the Arab and his jealousy of his honor, we find: Legislation Islam elevated women and demonstrated their great value, and that they are the sister of men in society and their companion in work and accounting. And chastity and jealousy are the most sublime things that legislation has immortalized, as long as it does not completely conflict with it. Invoking forbidden means for good purposes is not sufficient. He killed the Arab with the intention of getting rid of the disgrace of the purposes that were imaginary to him and which were not guaranteed to happen, so the Sharia wrote that they were invalidated. Explaining that Sharia law came to preserve souls and that it is one of the greatest universal goals that it takes into account both existence and non-existence. فلا يمتري أحد في أن العرب كانوا على الفطرة السوية، وحازوا مقاليد الكمال في مسائل الأخلاق، ولا جدال في أن الشرائع أتت لاستكمال فضائل الأخلاق وبيان علوّ منزلتها في حفظ نظام الأمم، بل إن الممحص لنصوص التشريع يجد ثمرات إيقاعها تزكية النفوس وتهذيبها، والأخلاق ملاك الأمر عند العرب في الجاهلية، ولأجل تحقيقها بذلوا نفيس الأنفاس من الأوقات والأموال وخاضوا الحروب والأهوال. (1) في بيان معاني مصطلحات البحث، عوّدنا اللسان العربي كثرة المفردات وتعاورها، ولعل من المهم في هذا البحث أن أورد المصطلحات التي استعملها العربي في التعبير عن الأخلاق السامية والراقية التي تعودها والتي خلص إليها فكره على أنها محط مفاخرة ومعيار سؤدد. ‌(2) الشواهد الشعرية المكرسة لمعاني العفة والغيرة، من أرقى مظاهر المروءة الغيرة والعفـة عند العربي وهذا لازم الاعتزاز والافتخار بالشرف وصون الأعراض، وقد روت لنا التواريخ أن التعدي على أعراض العربي يجر حروبا لا تخمد نيرانها. وفي ختام التطواف بهذا البحث المختصر عن عفة العربي وغيرته على عرضه نجد: أن التشريع رفع الإسلام المرأة وبين عظيم قدرها وأنها شقيقة الرجل في المجتمع وقرينته في العمل والحساب؛ وأن العفة والغيرة ما أرقى ما خلد التشريع ما لم يصادم أصلا كليا؛ والتذرع بالوسائل المحرمة لمقاصد حسنة لا يشفع، فوأد العربي بقصد التخلص من العار من المقاصد المتوهمة عنده والتي لا قطع بحصولها فكتب الشرع بإبطالها؛ وبيان أن الشريعة أتت للحفاظ على النفوس وأنها من أعظم المقاصد الكلية التي راعتها من جانب الوجود والعدم.